Organic Lasers: A High Performance Deep Blue Organic Laser Gain Material (Advanced Optical Materials 8/2017). Issue 8 (18th April 2017) - Wei, Qi; Li, Yan; Liu, Jingguan; Fang, Qiyun; Li, Jiewei; Yan, Xiaohong; Xie, Linghai; Qian, Yan; Xia, Ruidong; Huang, Wei
Abstract : It is difficult to realize both good optical and electronic features, because there is always a trade‐off between these two properties. In article number 1601003, Yan Qian, Ruidong Xia, Wei Huang, and co‐workers propose a novel molecular design strategy by introducing moderate steric hindrance to a π‐conjugated backbone to reach good balance between optical lasing property and carrier transporting characteristics.